Drawing food trends: Design potential in shaping food future. (October 2016) - Celi, Manuela; Rudkin, Jennifer
Highlights: Foresight and Advanced design (ADD) are both activities that aim to imagine the future. Design shapes food on three levels: material, immaterial but also prospective. ADD recognizes trend tool as method for social and design driven innovation. Trends are future signs that allow to take a step aside and to tackle boundaries. Design shapes food by transfer of trend elements from the known to the unknown. Abstract: Foresight and design are both activities that aim to imagine the future in response to change and uncertainty. Food—a basic human need- has engaged over time in an intrinsic relationship with the design discipline. Design and Food interact at several levels: material (product), immaterial (service) but also prospective (thought). Designers, along with other actors, shape the production, communication, packaging and distribution of food as well as the more ephemeral aspects of food consumption focused on the valorization of people's senses and experiences. Bearing in mind that each possible design intervention strongly impacts on environmental and social behaviors, the challenge here is to address the challenge of insuring durable innovation within complex social and technological dynamics. Through the lens of an Advanced Design practice, this paper raises the importance of reconsidering the definition of trends in order to build sustainable futures for food and thus for people. Trends are seeds of tomorrow scattered in the overwhelming detail of the present. 2 Modern societal trends 3 are drivers for adequate growth and continuous innovation. With a phenomenological approach this paper wants to show how the attention to trend can change food ways.